A dataset for methane concentrations and fluxes for alpine permafrost streams and rivers on the East Qinghai-Tibet Plateau - Liwei Zhang; Xinghui Xia; Shaoda Liu; Zhifeng Yang; Emily H Stanley; Peter A Raymond (Environmental Data Initiative, 2020)
This dataset is a collation of 3-year direct measurement values of CH4 concentrations and fluxes for EQTP streams and rivers, along with information on location, hydrological, physical, and chemical conditions of the study sites. Given the rarity and high value of this EQTP data set, it will be very valuable for the next update to global C flux estimates.